A Novel sRNA in Shigella flexneri That Regulates Tolerance and Virulence Under Hyperosmotic Pressure - Yang, Guang; Li, Boan; Jia, Leili; Qiu, Huaiyu; Yang, Mingjuan; Zhu, Binghua; Xie, Jing; Qiu, Shaofu; Li, Peng; Ma, Hui; Song, Hongbin; Wang, Ligui (Frontiers in Cellular and Infection Microbiology, 2020)
Regulation of the environmental stress response and virulence of Shigella flexneri may involve multiple signaling pathways; however, these mechanisms are not well defined. In bacteria, small regulatory RNAs (sRNAs) regulate bacterial growth, metabolism, virulence, and environmental stress response. Therefore, identifying novel functional sRNAs in S. flexneri could help elucidate pathogenic adaptations to host micro-environmental stresses and associated virulence. The aim of this study was to confirm the presence of an sRNA, Ssr54, in S. flexneri and to determine its functions and possible mechanism of action. Ssr54 was found to regulate tolerance and virulence under hyperosmotic pressure. Its expression was verified by qRT-PCR and Northern blotting, and its genomic position was confirmed by 5′-rapid amplification of cDNA ends. Ssr54 expression was significantly decreased (approximately 80%) under hyperosmotic conditions (680 mM NaCl), and the survival rate of the Ssr54 deletion strain increased by 20% under these conditions. This suggested that Ssr54 has been selected to promote host survival under hyperosmotic conditions. Additionally, virulence assessment, including guinea pig Sereny test and competitive invasion assays in mouse lungs, revealed that Ssr54 deletion significantly decreased S. flexneri virulence. A two-dimensional gel analyses suggested that Ssr54 may modulate the expression of tolC and ompA, thereby significantly decreasing S. flexneri virulence; meanwhile treF expression improves S. flexneri survival under different osmotic pressures. These results suggest that Ssr54 has a broad range of action in S. flexneri response to hyperosmotic environmental stresses and in controlling its virulence to adapt to environmental stresses encountered during host infection.